Corrosion Behavior of Stannate Conversion Coatings on AZ31B Alloys and Their Initial Discharge Performance as Anodes for Seawater Batteries. Issue 8 (11th August 2021) - Lu, Xiangyu; Hu, Jing; Zhao, Yang; Wang, Mai; Wang, Xiao; Ye, Zhanghan; Zheng, Zhiteng; Hu, Juanjuan; Feng, Xingguo
Abstract : Simple stannate solutions are employed to pretreat AZ31B alloys to improve their corrosion resistance behavior in the shelf stage and initial discharge performance as anodes for seawater batteries. The effects of the duration of the stannate treatment on the corrosion behavior and discharge performance of the alloys were investigated. Magnesium stannate conversion coatings were deposited on the alloys after different durations of stannate treatment and it was found that they reduce the corrosion rate of the alloys, thereby enhancing their storage stability. In the initial discharge process, the electrolyte can reach the AZ31B substrate easily through the discontinuities between stannate particles and the stannate conversion coatings have no negative effect on the activation of the Mg alloy anodes. In addition, a stannate treatment for 10 min can suppress the hydrogen evolution reaction and the negative difference effect to enhance the anodic utilization efficiency of alloys and their cell voltage. With the increasing discharge time, the exfoliation of the stannate particles refreshes the AZ31B alloys and the formation of metallic Sn improves the discharge performance.